Cognition, emotion, and Obstructive Sleep Apnoea Syndrome before and after severe weight loss treatment - Ribeiro, Olga Rodrigues; Costa, Paula; Carmo, Isabel do; Paiva, Teresa; Figueira, Maria Luísa (Sleep Science, 2022)
Introduction: This study aimed to compare the results of a conservative method and the Sleeve Gastrectomy procedure for weight loss on the cognitive-emotional performance of severely obese women assessed for Obstructive Sleep Apnoea Syndrome. Material and methods: Two samples consisting of females, approved for Sleeve Gastrectomy (n = 21) and Conservative Treatment (n = 21) underwent night polysomnography and completed a battery of neuropsychological and emotional tests before and 6 months after the interventions. We compared intra- and inter-sample results, post interventions result to controls, and treated patients with Obstructive Sleep Apnoea Syndrome.Results: Anthropometry, immediate memory, attention, executive functions, and emotional maladjustment improved after the interventions. The conservative method showed better results for inhibitory control, and surgery showed better results for cognitive flexibility, speed of information processing and general cognitive and emotional performance for women with Obstructive Sleep Apnoea Syndrome. Learning decreased following both interventions. Memory and cognitive flexibility were lower in the comparison group than in control groups.Discussion: Treatments impacted different cognitive domains with probable influence on the objectives achieved. Lower middle pressure for behaviour modification may have reduced learning after interventions. The reduction of depression/anxiety in women with Obstructive Sleep Apnoea may result from the improvement of the social effects of both conditions. Although with better results for the surgical method, anthropometric reductions in both methods, positively influenced the cognitive/emotional domains. The maintenance of cognitive weaknesses implies longer and more focused interventions to avoid the regression of results like the worsening of Obstructive Sleep Apnoea Syndrome.
Keywords: Cognition; Expressed Emotion; Sleep Apnea Syndromes; Weight Reduction Programs